(untitled) (ENTRENOVA - ENTerprise REsearch InNOVAtion Journal, 2017)
Typically, toy manufacturers use the color pink for girls’ toys and the color blue for boys. They also design gender-related theme worlds for girls and boys based on gender-based stereotypes, justified by different playing preferences of the two sexes. Socially-oriented toys such as dolls are meant for girls and non-social toys such as trucks are attributed to boys. In toy shops, early-stage shaping of the gender profile is thus achieved by color and theme design. This early-stage reinforcement and reproduction of gender stereotypes has been criticized because stereotyping can limit further child development and learning. The goal of this article is to examine the contribution of the color-setting and theme design to the perception of toys, the gender-related assignment as well as the preferences for playing with toys. For this purpose, the use of the eye-tracking technology is combined with a questionnaire. In an experiment six pairs of “LEGO®” models, which have been systematically varied in color and theme, are shown to 74 four- and five-year-old children. The results reveal that the original gender-stereotyped “LEGO®” models attract more attention among children than the varied gender-incongruent models. The original “LEGO®” models are clearly assigned to gender. In the case of the varied models, the color is more distinctive than the theme for gender classification and the interest in playing with the models. This work is licensed under a Creative Commons Attribution-NonCommercial 4.0 International License.